Students' perception of educational environment and its relationship to academic achievement in Cebu Institute of Medicine AY 2007-2008 - Tan-Meneses, Corazon T.; Nemuel S. Fajutagana MD MHPEd (2009)
Cebu Institute of Medicine (CIM) fully implemented the competency, problem-based learning (PBL) curriculum to its three year levels in school year 2003-2004. Genn (2001) stated that the environment of the school is a manifestation of the institution?s curriculum. Determination on how students experienced the educational environment generated by the PBL curriculum during school year 2007-2008 was determined by administering the 50-items Dundee Ready Education Environment (DREEM) inventory to the three year levels students. The objectives of this study were to: determine the perception of first- to third-year level CIM medical students on the educational environment under the innovative PBL curriculum and (2) determine whether there is a correlation between the students? perception of their educational environment and their academic achievement. This is a prospective cross-sectional and analytical study. No sampling of the population was done as all 219 first, second, third year students were the respondents for the DREEM Inventory, administered in March 2008. Statistical analysis with level of significance set at 0.05 was made through ANOVA, Chi-square, and t-tests, using the SPSS 14 and Microsoft Excel 2007 with Analysis ToolPak. Scatter plots were done and correlation factor was determined. Results revealed that the DREEM scores, global and subscale scores, across all three levels and between male and female students were not significantly different. The overall DREEM score was 135/200, a satisfactory category, denoting a relatively effective PBL curriculum. Proportion of each item category across year level and between sexes were done and significant differences were noted in certain items. The scatter plots showed that there was insignificant correlation between the DREEM scores and student achievement. In conclusion, the students as a whole perceived a positive educational learning environment in the PBL curriculum. The DREEM Inventory generated a ?profile? of strengths and weakness of the curriculum, and the tool can be used regularly to assess the curriculum.
Thesis (Master in Health Professions Education)--University of the Philippines Manila
Panel Members: Nemuel S. Fajutagana MD MHPEd, Chair/Adviser; Erlyn A. Sana PhD, Reader/Critic; Nomar M. Alviar MD MHPEd, Member; Maria Elizabeth M. Grageda PTRP MHPEd, Member; Armando C. Crisostomo MD MHPEd, Member.
Keywords: Academic achievement; Learning environment